1997
DOI: 10.1177/095624789700900213
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and caregiving: a framework for analysis and examples from southern and eastern Africa

Abstract: SUMMARY: This paper considers the role of caregiving on children's health and development with a special focus on identifying the constraints on effective caregiving in urban areas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Evidence from India, nonetheless, suggested that employed mothers were less likely to delay initiation of breastfeeding [40]. The relationship between maternal informal employment and EBF might be explained by the flexible working hours that mothers in the informal sectors have as it allows them to breastfeed their babies on demand [41]. However, subnational studies conducted in Ethiopia indicated that maternal employment was associated with lower odds of exclusive breastfeeding EBF [42, 43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from India, nonetheless, suggested that employed mothers were less likely to delay initiation of breastfeeding [40]. The relationship between maternal informal employment and EBF might be explained by the flexible working hours that mothers in the informal sectors have as it allows them to breastfeed their babies on demand [41]. However, subnational studies conducted in Ethiopia indicated that maternal employment was associated with lower odds of exclusive breastfeeding EBF [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…However, mothers residing in rural Bangladesh were more likely to initiate breastfeeding post-birth compared to their counterparts in urban Bangladesh [46]. A possible explanation for the decreased likelihood of EBF might be that metropolitan regions probably have a higher number of formally employed women [41].…”
Section: Discussionmentioning
confidence: 99%
“…Every year 10 million children die from preventable illness and more than half is accountable to malnutrition [2]. Infant undernutrition is a well-recognized public health problem in low- and middle-income countries (LAMIC) [3–5], the cause of which extends beyond mere shortage of food [3, 6, 7]. There are several factors implicated as cause of malnutrition and one of it and the neglected part is maternal mental disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Based on several previous theoretical path models (Brown & Pollitt, ; Engle, Menon, Garrett, & Slack, ; Walker et al., ), we developed a conceptual path model of potential influences on child development (Figure ). We tested the following pathways, which correspond to the labels of the arrows in Figure .…”
Section: Introductionmentioning
confidence: 99%